PERLAWANAN TERSAMAR ORGANISASI PETANI: SINERGI ANTARA KEPENTINGAN PEMBANGUNAN DAN ABSTRACT KEPENTINGAN GERAKAN SOSIAL - Purwandari, Heru; Kolopaking, Lala M; Tonny, Fredian (Sodality: Jurnal Sosiologi Pedesaan, 2012)
This study goal is understanding people movement development that articulated through organization construction. Farmer as social entity faced with structural pressure that obstruct the social transformation movement. According to the facing problems, these are natural when approach that developed by farmer organization is the community development strategy. Production center oriented for the latest 30 years have become the development ideology. Critic toward this paradigm as described above brought in to the community development (CD) approach. Unfortunately CD produce dependence with the elite structure and program, elite domination and effort to integrating farmer to high capital condition. Besides that problem, CD preserve community stability and disappear social change and social movement. Looking to this fact, farmer organization that prepared as case study develop a new paradigm for the community development which more intense to the people center development. This effort can be held with self govern building and farmer authority. Practically; choosing paradigm for people center development strategy. Differentiation between early CD with the CD as the strategy that will be directed to the people center development lie on the result. CD as the strategy is not resulting dependence otherwise achieving access and control to the resources. Those explanation above really want to describe that farmer achieving specific ways to reach organization goals. Paradigm resistance have been doing with the hidden tactic. Concept that founded in this research is disguised resistance. Disguised resistance indicated hidden strategy that used to reach organization agenda. Disguised resistance is the alliance model between maintaining social existence and the effort to the social deconstruction. Resistance have been doing bellow the government development propaganda and doing the redefinition to those propaganda in to the paradigm ways more oriented to the people center oriented. Keywords: Disguised Resistance, Farmer Organization, Farmer Self Govern, Farmer Authority